2002
DOI: 10.1046/j.1464-410x.2002.02798.x
|View full text |Cite
|
Sign up to set email alerts
|

Gender as a prognostic factor in patients with renal cell carcinoma

Abstract: Objective To evaluate gender as a prognostic factor in patients with renal cell carcinoma (RCC), using a retrospective review of patients with RCC stratified according to gender and analysing factors affecting prognosis. Patients and methods From January 1957 to December 1995, 768 patients with pathologically defined RCC (all of whom underwent nephrectomy) were classified as having clear cell carcinoma in 662 (follow-up in 648), papillary RCC in 43 (follow-up in 42), chromophobe cell carcinoma in 36 (follow-up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
18
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 22 publications
4
18
2
Order By: Relevance
“…However, BMI does not seem to contribute additional information to the established risk factors. Prognostic relevance of gender in favor of female patients, which has already been described previously by Onishi et al [30], was proven in our series.…”
Section: Discussionsupporting
confidence: 86%
“…However, BMI does not seem to contribute additional information to the established risk factors. Prognostic relevance of gender in favor of female patients, which has already been described previously by Onishi et al [30], was proven in our series.…”
Section: Discussionsupporting
confidence: 86%
“…These findings are consistent with previously reported results. [4][5][6][7][9][10][11] Moreover, these factors, except for sex, were found to be significant predictors of disease recurrence by univariate analysis; however, multivariate analysis showed that only the pathological stage was an independent predictor of recurrence. In fact, the recurrence rate after surgery increased in accordance with the increase in pathological stage in this series; that is, tumor recurrence was shown in 8.0%, 22.2%, and 52.5% of patients with pT1, pT2, and pT3 disease, respectively.…”
Section: Discussionmentioning
confidence: 87%
“…1,9,10 For example, Ljungberg et al 1 reported the usefulness of a follow-up protocol considering pathological stage and DNA ploidy, while Onishi et al 9 proposed a surveillance protocol mainly based on pathological stage combined with nuclear grade. However, to date, a consistent follow-up scheme for patients with RCC after surgical resection has not been available, due to the complicated biological characteristics of recurrent cases.…”
Section: Discussionmentioning
confidence: 99%
“…4,5,[7][8][9][10][11][13][14][15][16][17]30 Reports of a male survival advantage in cancer patients are rare. 31 The better survival of women with malignant diseases might just reflect their better general longevity, an earlier disease stage at diagnosis or a more favorable risk profile.…”
Section: Discussionmentioning
confidence: 99%
“…Recent examples are outcome in ischemic and nonischemic heart disease [1][2][3] and in solid neoplastic disorders such as malignant melanoma, [4][5][6] non-small-cell lung cancer treated with gefitinib and tipifarnib, [7][8][9] surgically treated colorectal cancer, 10 esophageal carcinoma, 11 renal cell carcinoma 12 and soft tissue sarcoma. 13,14 Gender differences in survival have been reported also in hematological malignancies such as Hodgkin's disease, 15 acute myeloid leukemia, 16 and childhood acute lymphoblastic leukemia.…”
Section: Introductionmentioning
confidence: 99%